Oxygen consumption, locomotory‐respiratory coupling and exercise‐induced pulmonary hemorrhage in horses during the Paso Fino gait - Shannon Massie; Renaud Léguillette; Warwick Bayly; Ray Sides; Angélica María Zuluaga‐Cabrera (Journal of Veterinary Internal Medicine)
Abstract Background Workload associated with the high frequency Colombian Paso Fino gait has not been evaluated. Objectives To determine the oxygen consumption (V̇O2), heart rate (HR), stride frequency: breathing ratio, and hematology associated with the Paso Fino gait, including whether exercise‐induced pulmonary hemorrhage (EIPH) occurs. Animals Eleven Paso Fino horses. Methods Prospective cohort study. Horses performed a standardized Paso Fino gait test across a wooden sounding board, simulating competition. V̇O2 and ventilatory parameters (tidal volume [VT]; peak inspiratory and expiratory airflows [PkV̇I, PkV̇E]; respiratory rate [RR], minute ventilation [V̇E]) were measured using a portable ergospirometry facemask. Heart rate was measured using electrocardiograms. Post‐exercise lactate, hematocrit, bicarbonate, pH, electrolytes, and biochemistry concentrations were measured. EIPH was assessed via tracheobronchoscopy. Four horses completed a secondary high‐intensity gallop to elicit peak V̇O2 for comparative purposes. Results Median [IQR] mean individual HR during the Paso Fino gait was 190 [178, 201] bpm. Relative V̇O2 measured 49.8 [48.4, 59.5] mL/(kg min; VT = 8.6 [8.0, 10.7] L; RR = 87.1 [75.4, 99.5] bpm; V̇E = 869 [740, 902] L/min; PkV̇I = 33.4 [32.7, 37.2] L/s; PkV̇E = 44.2 [40.3, 46.0] L/s). Horses took 2.8 [2.7, 2.9] strides/second and had a stride frequency: breathing ratio of 2.0 [1.8, 2.3]. Post‐exercise blood lactate concentration and hematocrit measured 2.7 mmol/L and 50% respectively. Three horses showed endoscopic evidence of Grade‐1 EIPH. The Paso Fino gait V̇O2 and HR equaled 79% V̇O2pk and 91% maximal HR, respectively, based on the high‐intensity gallop. Conclusions and Clinical Importance The Paso Fino gait represents submaximal exercise based on V̇O2 < V̇O2pk and blood lactate.